PENGARUH INFLASI, SUKU BUNGA DAN KURS TERHADAP INDEKS HARGA SAHAM GABUNGAN PERIODE JANUARI 2011 – FEBRUARI 2015 - Susan; J.P (Pasca Sarjana Universitas Satya Negara Indonesia, 2015)
The aim of this study is to proof the influence of macro-economic, especially inflation, interest rate and exchange rate to composite stock price index in Indonesia Stock Exchanges. The data observed are secondary from the online system from Januari 2011 up to Februari 2015. The analytical technique used is multiple regression analysis. The result of this study found that the rate of inflation, interest rates and exchange rate are simultaneously have significantly influence on composite stock price index with Adjusted R 2 of 0,658, which means that 65,8% variance of composite stock prices index can be explained by the 3 variables and the rest is out this study. Partially, found that the variable inflation rate does not influence on composite stock price index, while the variable interest rates has a negative and siginficant influence on the composite stock price index, and the variable rate has a positive and significant influence on composite stock price index.